Pembelajaran Pendidikan Agama untuk Anak TK Melalui Media Pembelajaran Cerita Naratif - Farwati, Wiwik Wida; Alawiyah, Rosidah; Hayati, Ridha Nurul; Cahyani, Arie; Elthia, Memy Wardani (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
One of the methods used by teachers to instill religious moral values in children is through story activities. The need to inculcate religious morals in the story method is expected to make the values taught can be internalized and interpreted by children without coercion. The purpose of this study was to find out the implementation of the story method in instilling religious morals in early childhood in Al-Falah Panumbangan kober, as well as to find out the strengths and weaknesses when the story method is used in learning at school. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. The findings from this study are that storytelling activities can develop religious morals in early childhood when activities are carried out with the right delivery and choosing the right stories. Efforts made by teachers to instill religious morals in early childhood so that children can understand and practice them in everyday life. So that the implementation can be done by the teacher by choosing the right story.